REHUMANISASI MELALUI PENDIDIKAN AGAMA MENURUT PERSPEKTIF KH. AHMAD DAHLAN - Abdul Rahman jupri; Zamah Sari (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2022)
ABSTRACTThe importance of prioritizing humanization in the religious learning process aims so that students do not experience dehumanization. Rehumanization is intended so that students have complete rights and obligations in carrying out religious learning in the classroom. The purpose of this study is to describe rehumanization through religious education from the perspective of KH. Ahmad Dahlan. This study uses a descriptive analysis approach with a literature review research model (library research). The results of this study are according to Dahlan, religious education must be taught in an integrative way with other sciences, religious education must be taught physically and mentally in order to provide a complete concept to humans, religious education must be able to prioritize unity of heart so that it becomes a unifier of all differences, and religious teaching in schools must cover faith, teach love to fellow human beings, religious learning must revive the mind, religious learning must teach independence so that humans can rule and control themselves.Keywords: Rehumanization, Humanization, Religious Education